2013
DOI: 10.3109/02699052.2013.826505
|View full text |Cite
|
Sign up to set email alerts
|

Connecting family needs and TBI caregiver mental health in Mexico City, Mexico

Abstract: Interventions for TBI caregivers, especially in Latin America, should help family members determine how best to meet their health information and instrumental needs, with the former being likely to improve caregiver mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 44 publications
0
37
3
1
Order By: Relevance
“…The European and the American findings are in contrast to a recent Mexican study that found the emotional needs were mostly met and the most unlikely met needs were from the sub-scale 'Health Information' [38]. The findings suggest that relatives receive ample medical information, but are less likely to receive adequate emotional and professional support.…”
Section: Met Ratingscontrasting
confidence: 89%
See 1 more Smart Citation
“…The European and the American findings are in contrast to a recent Mexican study that found the emotional needs were mostly met and the most unlikely met needs were from the sub-scale 'Health Information' [38]. The findings suggest that relatives receive ample medical information, but are less likely to receive adequate emotional and professional support.…”
Section: Met Ratingscontrasting
confidence: 89%
“…This is consistent with another European study [19] which reported the percentage of 46% of the important rated needs as met. The other studies using the FNQ [6,26,38] did not combine the importance and met ratings, consequently a comparison with these samples is not possible.…”
Section: Met Ratingsmentioning
confidence: 99%
“…Clinical cutoffs grade burden severity as mild (range: 0-20), mild to moderate (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), moderate to severe (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), and severe burden (61-88). 33 The baseline characteristics of the patients and their caregivers are displayed in Table 1.…”
Section: Informal Caregiver Burden Assessmentmentioning
confidence: 99%
“…Similarly, high rates of depression have been reported among carers of people with disabilities, including parents and spouses, following the onset of ABI [10]. The causes for depression in carers relate to the lack of instrumental supports provided to the caregivers as they learn to manage the changes in their loved one [11]. The challenge for people with ABI and their carers is that psychiatric disorders can persist for years following the ABI [7,12,13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These emotional and behavioural issues impact negatively on recovery and rehabilitation following ABI [9,[15][16][17][18][19], including the ability to resume former roles in the community [9][10][11][12][13][14][15][16][17][18][19], quality-of-life [4,20,21] and life satisfaction [22]. These issues are often long-term problems for people with dual diagnosis [5,23].…”
Section: Literature Reviewmentioning
confidence: 99%